Aberrant Histone Methylation in Patients with Graves' Disease. (24th June 2019) - Yan, Ni; Mu, Kaida; An, Xiao-fei; Li, Ling; Qin, Qiu; Song, Rong-hua; Yao, Qiu-ming; Shao, Xiao-qing; Zhang, Jin-an
Abstract : Background . Graves' disease (GD) is an organ-specific autoimmune disease. Accumulated data have indicated that aberrant epigenetic modifications are associated with many autoimmune disorders. However, it remains unknown whether histone methylation plays a role in the pathogenesis of GD. In the present study, we aimed to assess histone modification patterns in peripheral blood mononuclear cells (PBMCs) from GD patients. The rate (degree) of H3K4 and H3K9 methylation and the expressions of histone-modifying genes were investigated. Methods . A total of 68 GD patients and 32 healthy controls were enrolled in this study. Global histone H3K4/H3K9 methylation of PBMCs was evaluated by the EpiQuik™ global histone H3K4/H3K9 methylation assay kit. The expressions of histone methyltransferases (HMTs) and histone demethylases (HDMs) at the mRNA level were determined by real-time quantitative polymerase chain reaction. Results . Global histone H3K9 methylation in PBMCs of GD patients was significantly decreased compared with that in the healthy controls (P=0.007). The expressions of HMTs (SUV39H1 and SUV39H2) at the mRNA level were significantly decreased in PBMCs from GD patients compared with healthy controls (P<0.001), whereas the SETD1A expression at the mRNA level was significantly increased in GD patients compared with healthy controls (P=0.004). In addition, the expressions of HDMs, including JHDM2A and JMJD2A, at the mRNA level were significantly increased in GD patients compared with healthy controls (P<0.001; P=0.007). Moreover, the mRNA expression levels of JARID1A and LSD1 did not significantly differ in GD patients and healthy controls (P>0.05). Conclusions . These findings firstly suggested that the histone methylation was aberrant in PBMCs of GD patients, which could be possibly attributed to the deregulation of epigenetic modifier genes. Abnormal histone methylation modification may be involved in the pathogenesis of GD.